Organized civil society, public politics and politics of health in Brazil - Vera Viviane Schmidt (INTERthesis, 2006)
The structure of the Brazilian Public Health has been built in the interrelation State and Society, going by countless transformations to reach the configuration that today if it presents us. The government's representatives, institutions of health and the organized civil society, they have been making to represent their interests in front of the State that appears as mediator, executioner and/or backer of the social public politics. The reached results represent the consolidation of interests, through the weight of the ideas and of the involved actors. With the democratic opening and the political-administrative reforms that are followed the promulgation of the current Federal Constitution, the politics of health have been reaching a more democratic character and more universal that the precedent.